Optimalization of Revenue Forecasting in the Security of the Parliament - A. Rasyid, Sofya; Marliyah, Marliyah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2019)
Currently, the government of the Parigi Moutong Regency has sought to facilitate access to community forest plants that are truly managed by the community rather than the financiers. "Around 80% of the poor population in Central Sulawesi around the forest that can be managed by the community has now been designated as a community forest plantation area. Communities living around the forest must be empowered to increase their income and welfare to reduce poverty. This study aims to find out how much is the optimum income (Z) of community forest farming, find out how much (land capacity) at the time of optimum income, find out what is the residual value of using production facilities at the time of optimum income, find out the sensitivity value of income per hectare of community forest farming and know the sensitivity value of community forest farming production facilities. Research in the village of Suli, Balinggi Subdistrict, Parigi Moutong District with the object of research is the community forest farming system of monoculture and agroforestry with the composition of Nyatoh stands (Palaquium spp), and Cocoa (Theobroma cacao, L). The optimum net income (Z) for community forest farming is Rp. 731,692,400 with an area of 3 ha over a 20-year cycle. The maximum income of community forest farming is achieved by a combination of a nyatoh monoculture farming model with an area of 1.16 ha, cocoa agroforestry with an area of 0.9 ha, and monoculture cocoa with an area of 0.94 ha. Optimum income will not change if farm income is real with an income of Rp. 286,900,000 - increased by unlimited or reduced to Rp. 246,072,500. Real agroforestry and cocoa with an income of Rp. 326,900,000, - if raised to Rp. 392,224,000, - or reduced by unlimited, - Cocoa with an income of Rp. 111,360,000 - increased to Rp. 120,009,335. The sensitivity value indicates that an increase in 1 unit of production facilities for land and TSP will increase the optimum income value, while for seeds, cocoa seedlings, hole making, planting, manure, insecticide, maintenance 3x a year, NPK, Urea, KCL, thinning, cocoa harvesting and harvesting, if it is increased indefinitely it will reduce the value of optimum income because each additional inventory will be the remaining value of the inventory